REVISITANDO DIAGRAMAS DE CASUALIZAÇÃO E DE HASSE PARA O PLANEJAMENTO DE EXPERIMENTOS E ANÁLISE DE DADOS - SERMARINI, Renata Alcarde; PIEDADE, Sônia Maria De Stefano; DEMÉTRIO, Clarice Garcia Borges; SANTOS, Alessandra dos (Brazilian Journal of Biometrics, 2017)
The randomization diagrams and the Hasse diagrams are graphic tools that help to construct the analysis of variance table. Using randomization diagrams, we can identify the confounding between factors and the explicit randomization used on the experiment. With the Hasse diagrams we can see the relation between factors (crossed or nested) and calculate the number of degrees of freedom, obtain the expression for sums of squares and expected mean squares, for each source of variation. This paper joins this two tools and presents three application examples, highlighting the facility in using them and the importance of building randomization based models.